Model Kebijakan Fiskal Islam Berbasis Keadilan Sosial: Analisis Ekonomi dan Syariah - Siti Nur Rohmah; Hilyawan Prada Putra Akbar; M. Abdillah Hanif (Jurnal Penelitian Ilmu Ekonomi dan Keuangan Syariah, 2025)
This study explores the approach of fiscal policy within the framework of islamic economics, emphasizing the faundation of social justice. In this context, the state’s role goes beyond regulating the economy through instrumens such as expenditure and taxation; it also involves upholding Sharia principles that balance both spirituak and material implementation of tools like zakat, infaq, and sadaqah in wealth redistribusion and strengthening the economic stability of the ummah. This research employs a qualitative method using literature review from various academic sources. The findings indicate that islamic fiscal policy priotirizes justice, efficiency, and moral responcibility as the basis for creating collective welfare. Zakat is shown to be a vital instrument-not onlu as a form of woship but also for its tangible is believed to offer a viable alternative is believed to offer a viable alternative to address modern economic inequality.